THE COMPREHENSIVE SAFETY EVALUATION METHOD BASED ON THE DEFECT QUANTITATIVE FOR THE PRESSURE VESSEL IN SERVICE - LIU Jun; HUANG Chen; CHENG ShaoWei; ZHANG XiaoHong; HE Xing (Jixie qiangdu)
The magnetic memory testing and fuzzy evaluation theory is applied to the comprehensive safety evaluation of pressure vessel in service,and a comprehensive safety evaluation model of the pressure vessel in service is established. The defect parameters of pressure vessel in service are obtained using the magnetic memory testing method and the corresponding defect quantitative formula. The membership degrees of fatigue and fracture failure are solved based on the assessment method of fatigue and fracture of pressure vessel in service. Then according to the established factor set,evaluation set and weight set,the comprehensive safety assessment of pressure vessels in service is realized using the weighted average method. Finally,the comprehensive safety evaluation method based on the defect quantitative for the pressure vessel in service is got and an example is provided.